Matching Apictorial Puzzle Pieces Using Deep Learning - CHIȘ, Raluca-Diana (Studia Universitatis Babeș-Bolyai Informatica, 2024)
Finding matches between puzzle pieces is a difficult problem relevant to applications that involve restoring broken objects. The main difficulty comes from the similarity of the puzzle pieces and the very small difference between a pair of pieces that almost match and one that does. The proposed solution is based on deep learning models and has two steps: firstly, the pieces are segmented from images with a U-Net model; then, matches are found with a Siamese Neural Network. To reach our goal, we created our own dataset, containing 462 images and just as many masks. With these masks, we built 3318 pairs of images, half of them representing pieces that fit together and half that do not. Our most relevant result is estimating correctly for 290 out of 332 pairs whether they match. Received by the editors: 23 October 2023. 2010 Mathematics Subject Classification. 68T45, 68U10. 1998 CR Categories and Descriptors. I.2.10 Artificial Intelligence: Vision and Scene Understanding – Shape; I.4.6 Image Processing and Computer Vision: Segmentation – Edge and feature detection.